Evaluación técnica de un fluido de perforación base agua utilizando como aditivo nanopartículas de óxido de grafeno a escala de laboratorio para la inhibición de lutitas en los Campos Castilla y Chichimene de Ecopetrol S.A. (2017)
The project was focused on a type of applied research, whose main objective was to evaluate graphene oxide as nanomaterial and additive in a water-based drilling fluid to improve shale inhibition and well stability; During the investigation two types of graphene oxide were evaluated, the first corresponded to the one synthesized by the Hummers method (HXS-1), and the second one to an imported commercial product (HX-1), taking into account the following selection parameters : Presentation, purity and cost. The nanomaterials were characterized by SEM, TGA, XRD, Raman, elemental and IR characterization techniques in order to corroborate the quality of the synthesized and imported product. The experimental process was carried out in two experimental stages, in order to evaluate the nanomaterial through laboratory tests established by API RP 13B-1.